The Higher Education Institution for a Sustainable Future: A Comparative Study from Indonesia and the Philippines on Advancing the SDG - Nina Yulianti (PT Keberlanjutan Strategis Indonesia, 2026)
The 2030 Agenda for Sustainable Development, with SDG 4 (Quality Education) as a foundational goal, requires significant contribution from Higher Education Institutions (HEIs) through research, innovation, and community engagement promoting sustainability. This study utilizes a comparative method to analyze sustainability leadership within HEIs in Indonesia and the Philippines, revealing both progress and persistent inequalities. The increasing inclusion of universities in global sustainability rankings signifies institutional transformation that integrates environmental stewardship, social inclusion, and educational innovation. Leading HEIs—such as Universitas Indonesia, Universitas Gadjah Mada, De La Salle University–Dasmariñas, and the University of the Philippines—exemplify measurable sustainability leadership. However, this progress remains highly concentrated in urban and well-resourced regions (Java and Luzon), reflecting spatial and institutional disparities that limit national participation. Comparative analysis indicates that Indonesian HEIs, notably Universitas Gadjah Mada and IPB University, demonstrate a more balanced sustainability performance across social and environmental dimensions, reflecting cohesive national coordination, while Philippine universities display specialized yet uneven achievements. To sustain momentum, both countries must strengthen inclusive policies, inter-university collaboration, and regional capacity building to empower HEIs as equitable and effective agents of sustainable development, reinforcing a shared vision for a resilient and inclusive future